The Analysis of Tilapia Exports on Regional Original Revenue (ROR) of Dairi Regency, North Sumatra - Ahmad Fadlan; Andika Pratama (Lead Journal of Economy and Administration, 2024)
This research was conducted in Dairi Regency, North Sumatra. The purpose of this study was to determine the Export factors on local revenue of the Dairi Regency of North Sumatra. this uses quantitative and qualitative data and the model used is Path Analysis which is operated through the SPSS Version 25.0 for Windows program. In this study, the data collection method used was using a questionnaire with a Likert scale. The number of samples used was 20 tilapia fish entrepreneurs, the data collected by distributing questionnaires. Based on the results of path analysis testing directly Capital, Exchange Rates, Inflation, Exports, Production, Prices directly have a significant and positive effect on Regional Original Income (ROR), the purpose of this study is to analyse the effect of ROR on Capital, exchange rates, inflation, export production of tilapia prices in the Dairi district of North Sumatra. in this study shows that there are only two 2 variables that affect the regional original income of the dairi district, namely exports and selling prices that have a significant effect on the regional original income of the dairi district of North Sumatra. While capital, exchange rates, inflation, production have an insignificant effect on the local revenue of the Dairi district of North Sumatra.